(untitled) (Journal of actual problems of jurisprudence, 2018)
The article deals with the subjective features of crimes with a double form of guilt, analyzed the validity of allocation of crimes with two forms of guilt in the new criminal legislation of the Republic of Kazakhstan. Abstract ratio (contrast) of crimes with two forms of guilt with an ideal set of crimes. Also in the article the question of the legal consequences of crimes to form a double fault and the problem of subjective imputation in criminal law. Key words: guilt, criminal liability; the offense with two forms of guilt; the ideal set of crimes.